2018
DOI: 10.1007/s11664-017-6023-6
|View full text |Cite
|
Sign up to set email alerts
|

Interface-Dependent Effective Mobility in Graphene Field-Effect Transistors

Abstract: By pretreating the substrate of a graphene field-effect transistor (G-FET), a stable unipolar transfer characteristic, instead of the typical V-shape ambipolar behavior, has been demonstrated. This behavior is achieved through functionalization of the SiO 2 /Si substrate that changes the SiO 2 surface from hydrophilic to hydrophobic, in combination with postdeposition of an Al 2 O 3 film by atomic layer deposition (ALD). Consequently, the back-gated G-FET is found to have increased apparent hole mobility and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The reason for this is because the mobility signature shown in Figure 4b is nonmonotonic, meaning that if bias stressing was causing the change in mobility, the signal would trend in one direction only and not increase again in mobility after a precipitous drop. Ahlberg et al 38 showed that by top gating an Al 2 O 3 −graphene heterostructure (also back-gated), they were also adjusting the graphene mobility by adjusting the bias of the top-gate between −2 and + 2 V. Given the high gain of our device, only a small number of photons are needed to create a significant build up of charge within the perovskite layer, which would then change the mobility of the charge carriers in the graphene layer, analogous to Ahlberg et al The ambient photons incident on the perovskite layer are not saturating the perovskite layer with minority charge carriers, as the conditions of the experiment were done in the dark; the relatively small number of photons affecting the perovskite was fluctuating, which could explain the nonmonotonic signal of the graphene's mobility.…”
Section: = × Attenuation (%) (1 Ementioning
confidence: 99%
“…The reason for this is because the mobility signature shown in Figure 4b is nonmonotonic, meaning that if bias stressing was causing the change in mobility, the signal would trend in one direction only and not increase again in mobility after a precipitous drop. Ahlberg et al 38 showed that by top gating an Al 2 O 3 −graphene heterostructure (also back-gated), they were also adjusting the graphene mobility by adjusting the bias of the top-gate between −2 and + 2 V. Given the high gain of our device, only a small number of photons are needed to create a significant build up of charge within the perovskite layer, which would then change the mobility of the charge carriers in the graphene layer, analogous to Ahlberg et al The ambient photons incident on the perovskite layer are not saturating the perovskite layer with minority charge carriers, as the conditions of the experiment were done in the dark; the relatively small number of photons affecting the perovskite was fluctuating, which could explain the nonmonotonic signal of the graphene's mobility.…”
Section: = × Attenuation (%) (1 Ementioning
confidence: 99%